Photocatalysis : fundamentals and perspectives - Schneider, Jenny; Bahnemann, D.; Ye, Jinhua; Puma, Gianluca Li; Dionysiou, Dionysios D. (RSC energy and environment series ;, 2016)
Combining the basic concepts of photocatalysis with the synthesis of new catalysts, reactor and reaction engineering, this book provides a comprehensive resource on the topic. The book introduces the fundamental aspects of photocatalysis including the role of surface chemistry and understanding the chemistry of photocatalytic processes before exploring the theory and experimental studies of charge carrier dynamics. Specific chapters then cover new materials for the degradation of organics; water splitting and CO2 reduction; as well as reactor and reaction engineering. Researchers new to this discipline can learn the first principles, whilst experienced researchers can gain further information about aspects in photocatalysis beyond their area of expertise. Together with Photocatalysis: Applications, these volumes provide a complete overview to photocatalysis.